Functionalized Mn3O4 Nanosheets with Photothermal, Photodynamic, and Oxidase‐Like Activities Triggered by Low‐Powered Near‐Infrared Light for Synergetic Combating Multidrug‐Resistant Bacterial Infections. Issue 12 (26th February 2022) - Zhang, Xinwen; Min, Yuanhong; Zhang, Qi; Wu, Shiyue; Fu, Wensheng; Wu, Jiangling; Li, Ming; Wang, Yi; Zhang, Pu
Abstract: Multidrug‐resistant (MDR) pathogenic bacterial infections have become a major danger to public health. Synergetic therapy through multiple approaches is more powerful than the respective one alone, but has been rarely achieved in defeating MDR bacterial infections so far. Herein, indocyanine green‐functionalized Mn3 O4 nanosheets are engineered as an efficient and safe antibacterial agent with photothermal, photodynamic, and oxidase‐like activities, which display powerful ability in treating MDR bacterial infections. Therein, photothermal and photodynamic activities can be triggered by a single low‐powered near‐infrared laser (808 nm, 0.33 W cm −2 ), resulting in the generation of localized hyperthermia (photothermal conversion efficiency, 67.5%) and singlet oxygen. Meanwhile, oxidase‐like activity of this material further leads to the generation of hydroxyl radical as well as superoxide radical. Sheet‐like structure with rough surfaces make them tends to adhere on bacterial surface and thus damage membrane system as well as influence bacterial metabolism. As a result, Gram‐positive and Gram‐negative bacteria can both be eradicated. Animal experiments further indicate that the functionalized Mn3 O4 nanosheets can effectively treat methicillin‐resistant Staphylococcus aureus ‐infected wounds through the triple synergetic therapy. Moreover, toxicity evaluation in vitro and in vivo has proved the superior biosafety of this material, which is promising to apply in clinical anti‐infective therapy. Abstract : Mn3 O4 nanosheets‐based photothermal/photodynamic /nanozymatic synergetic antibacterial nanoplatform is engineered, which can efficiently convert near‐infrared light into high heat and generate three kinds of reactive oxygen species under a single 808 nm laser with power density as low as 0.33 W cm −2 . This platform demonstrates strong power in eradicating multidrug‐resistant bacteria and promoting wound healing in vivo.